2016
DOI: 10.1039/c6cc05709h
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and irreversible emergence of chiroptical signals in J-aggregates of achiral 4-sulfonatophenyl substituted porphyrins: intrinsic chirality vs. chiral ordering in the solution

Abstract: Mueller matrix polarimetry distinguishes the different origins of the reversible and irreversible chiroptical effects emerging in stirred solutions of J-aggregate nanoparticles: the reversible effect is due to an anisotropic ordering in the solution and the irreversible one is due to a bias from the racemic composition of intrinsically chiral structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Recent Mueller matrix results modify previous reports on the alignment of the J‐ and H‐exciton bands in the H 4 TPPS 4 J‐aggregate nanotubes . This, together with the observation that only long shaped nanotubes can be oriented in the stirring flows, allowed a qualitative simulation of the nanotube alignment determined by the hydrodynamics in the stirred cuvette (Figure ). The model assumes that two vortexes of opposite chiral sign are present in a vortex stirred cuvette, a central descending one and an ascending one at the walls region.…”
Section: Hydrodynamic Effectsmentioning
confidence: 55%
See 1 more Smart Citation
“…Recent Mueller matrix results modify previous reports on the alignment of the J‐ and H‐exciton bands in the H 4 TPPS 4 J‐aggregate nanotubes . This, together with the observation that only long shaped nanotubes can be oriented in the stirring flows, allowed a qualitative simulation of the nanotube alignment determined by the hydrodynamics in the stirred cuvette (Figure ). The model assumes that two vortexes of opposite chiral sign are present in a vortex stirred cuvette, a central descending one and an ascending one at the walls region.…”
Section: Hydrodynamic Effectsmentioning
confidence: 55%
“…b) Example of simulations of chiroptical responses of macroscopic helical arrangements of nanotubes. In all cases, the nanotube near to the wall is according to the orientation given by Mueller matrix microscopy imaging of the wall deposits obtained under stirring; for more details see ref …”
Section: Hydrodynamic Effectsmentioning
confidence: 99%
“…In the former case, the stereochemical course of the self-assembling process is governed by the presence of chiral groups linked on the porphyrin peripheral frame (Oliveira-González et al, 2015;van der Weegen et al, 2017). In the latter issue, final chiral suprastructures are obtained by interaction of achiral substrates with external physical effectors, such as hydrodynamic directional forces (Sorrenti et al, 2012;Arteaga et al, 2016); magnetic fields (Micali et al, 2012); LB and LS techniques (Chen et al, 2011), or chiral molecular templates, such as surfactants (El-Hachemi et al, 2008), chiral polymeric matrices (D'Urso et al, 2012), chiral ligands (Borovkov and Inoue, 2006;Berova et al, 2007) or carboxylic acids (Castriciano et al, 2011). With this regard, Monsù Scolaro showed that the assembly of a non-chiral porphyrin derivative templated by the two different enantiomers of tartaric acid proceeds with different kinetics and results in final chiral suprastructures with highly different anisotropy factors, which are strictly dependent on the enantiomer used as a templating agent (Castriciano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike these two kinds of vortex‐responsive system, a third kind of system was reported by several labs, showing dynamic and switchable chiroptical properties and the ability to turn them ON/OFF by controlling the vortex stirring [8f–n] . The third kind of vortex‐responsive system always includes nanoscale assemblies that possess anisotropic morphologies, such as fibers.…”
Section: Introductionmentioning
confidence: 99%
“…After decades of study, Ribó et al. pointed out that the chiroptical properties of those systems were generated by the dynamic chiral arrangement of nanoscale assemblies in the vortex flow [8j,n] . The limiting Curie groups were adopted for discussion [12] .…”
Section: Introductionmentioning
confidence: 99%